Under-Age Children Returning From Jihadist Group Operation Areas: How Can We Make a Diagnosis and Construct a Narrative With a Fragmentary Anamnesis? - Klein, Anaelle; Mapelli, Alessandra; Veyret-Morau, Maurween; Levy-Bencheton, Julie; Giraud, François; di Chiara, Mercedes; Fumagalli, Marta; Lida-Pulik, Hélène; Moscoso, Ana; Payen de la Garanderie, Jérôme; Palazzi, Stephanie; Baleyte, Jean-Marc; et al. (Frontiers in Psychiatry, 2020)
INTRODUCTION: Since 2011, the French government estimates that about 500 French children were born or were taken by their parents to areas where terrorist operations prevail. Since May 2017, 75 children who returned to France have benefited from a specific health care system. METHOD: This article is the result of clinical interviews conducted with 53 patients evaluated and taken care of at Avicenne Hospital in Bobigny. To our knowledge, no studies have been published on this subject. RESULTS: 32 evaluations have been completed, all of which indicated the need for care for these children. 64% of these children are under 5 years old. 59% were born in France. The clinical pictures, heterogenous, fluctuate with time. DISCUSSION: The multiple adverse events experienced by children and the uniqueness of children born to families suspected by authorities of having participated in activities related to terrorism make this situation unprecedented. How can we make a diagnosis of PTSD without the help of a precise anamnesis? How can we help these children form a structuring narrative that avoids the pitfalls inherent to generalized fascination?